Sanusi movement and foreign affairs relations and its role in the independence of Libya 1886-1951 / Adel A Mohamed Elshbli - Adel A , Mohamed Elshbli (2018)
This study, in its four chapters, examines the topic of the Sanusi movement, its external relations and its role in the independence of Libya. That is done by tracing Sanusi movement’s influence, its reform efforts, as well as its military and political efforts that ultimately led to the independence, and the establishment of the United Kingdom of Libya, which, at that time, was an example of the modern state of Libya. The problem of this research is to highlight and analyze the nature of the external relations of the Sanusi movement and to reveal its role under colonial domination, by highlighting the distinguished leadership role of its leaders and its struggle for independence and the establishment of the United Kingdom of Libya in 1951. The study aims to find out the truths about a number of issues, most important of which is the nature of the external relations of the Sanusi movement and its position towards other Islamic movements. It also aims to highlight the role of the movement and its leadership in resisting the Italian occupation in Libya. The third aim is to reveal the Sanusi movement’s political role domestically and internationally in the independence of Libya. The researcher followed the historical descriptive and analytical approach in order to paint a clear picture of those political and historical events that the Sanusi movement lived in, and to examine the movement’s external relations during the period of time under study. The research reached several conclusions. Most important of them is that the Sanusi movement was established as a reformist religious preaching movement. Then, the domestic and international circumstances changed. That had its effect on the religious preaching movement that led it to later on take up political activities. The study concluded that the Sanusi movement managed to establish foreign relations with international powers, especially with Britain. These relations were based on national interest and the on necessity of seeking to gain that Sanusi movement, through its military and political struggle, was able to achieve the independence of Libya in 1951. As for further study, the researcher made a number of recommendations, in the hope that other researchers would benefit from the subject. Most important of which is that a study of the individual external relations of the Sanusi movement with countries such as Britain should be carried out with deep focus, and the effects of these relations on the political and military track of the Sanusi movement at the local and international levels be identified, so as to contribute to others’ research delving into the study of those relationships in detail the independence of the country.